Elucidating the optical, electronic, and photoelectrochemical properties of p-type copper vanadate (p-Cu5V2O10) photocathodes. Issue 25 (17th June 2020) - Song, Angang; Berglund, Sean P.; Chemseddine, Abdelkrim; Friedrich, Dennis; Abdi, Fatwa F.; van de Krol, Roel
Abstract : Compact spray-pyrolysed Cu5 V2 O10 photocathodes with 1.9 eV bandgap show positive photocurrent onset voltage and promising photoresponse. Abstract : P-type copper vanadate (Cu5 V2 O10 ) photoelectrodes made by spray pyrolysis were developed and evaluated as a potential photocathode material for photoelectrochemical (PEC) water splitting. Using fluorine-doped tin oxide as a substrate, highly phase-pure p-Cu5 V2 O10 thin films were obtained after annealing at 550 °C for 4 hours in air. Cu5 V2 O10 has a small bandgap energy in the range of 1.8–2.0 eV, allowing it to absorb visible light and making it potentially interesting for solar water splitting applications. The p-Cu5 V2 O10 films were characterized by photoelectrochemical techniques in order to provide insight into the critical PEC properties such as the flat-band potential, chemical stability, and incident photon-to-current efficiency (IPCE). The best-performing films showed a photocurrent density of up to 0.5 mA cm −2 under AM1.5 simulated sunlight, and an IPCE value up to 14% for 450 nm light at 0.8 VRHE with H2 O2 as an electron scavenger. Despite the narrow band gap and suitable conduction band edge position for PEC H2 production, these p-type films were unstable under constant illumination in aqueous electrolyte (pH 6.8) due to the reduction and dissolution of Cu. Based on our findings, the suitability of Cu5 V2 O10 as a photocathode material for photoelectrochemical water splitting is critically discussed.